2022
DOI: 10.1002/ctm2.1101
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing reveals cellular and molecular reprograming landscape of gliomas and lung cancer brain metastases

Abstract: Background Brain malignancies encompass gliomas and brain metastases originating from extracranial tumours including lung cancer. Approximately 50% of patients with lung adenocarcinoma (LUAD) will eventually develop brain metastases. However, the specific characteristics of gliomas and lung‐to‐brain metastases (LC) are largely unknown. Methods We applied single‐cell RNA sequencing to profile immune and nonimmune cells in 4 glioma and 10 LC samples. Results Our analysis revealed that tumour microenvironment (TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 103 publications
(156 reference statements)
2
13
0
Order By: Relevance
“…Cancer cells and cells in the tumor microenvironment collectively determine disease progression and response or avoidance to treatment ( 10 ). scRNA-seq including glioma and LUAD brain metastasis mainly focus on the non-tumor cells reported LUAD BM reprogramed cells into immune suppressed state, and immunotherapy could potentially an effective treatment ( 48 ). Study on tumor cell at cell level may provide target of tumor cells, combined with immunotherapy which may improve treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells and cells in the tumor microenvironment collectively determine disease progression and response or avoidance to treatment ( 10 ). scRNA-seq including glioma and LUAD brain metastasis mainly focus on the non-tumor cells reported LUAD BM reprogramed cells into immune suppressed state, and immunotherapy could potentially an effective treatment ( 48 ). Study on tumor cell at cell level may provide target of tumor cells, combined with immunotherapy which may improve treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…BD Rhapsody system (BD Biosciences) was used to obtain the single‐cell transcriptomic expression profile from glioma tissues in accordance with the protocol provided by the manufacturer, and the details were described in the previous study 14 . In short, immediately after the resection by professional neurosurgeons, fresh tumor tissue specimens were rapidly transported to the lab on ice, followed by mincing, digesting, and suspending.…”
Section: Methodsmentioning
confidence: 99%
“…These neutrophils exhibit activated HIF-1 signalling pathways by expressing HIF1A, lactate dehydrogenase A, VEGF-A, which are significant pro-angiogenic factors. 61 Taken together, angio-genesis is the result of the interaction of multiple TME components. Thus, targeting the TME may provide new ideas for the anti-angiogenic approaches.…”
Section: Tme-derived Factorsmentioning
confidence: 99%
“…A recent single‐cell sequencing‐based study showed a neutrophil cluster characterised by reactive oxygen species‐production in the lung cancer brain metastasis microenvironment. These neutrophils exhibit activated HIF‐1 signalling pathways by expressing HIF1A, lactate dehydrogenase A, VEGF‐A, which are significant pro‐angiogenic factors 61 . Taken together, angiogenesis is the result of the interaction of multiple TME components.…”
Section: Ec–tumour Cell Interactionmentioning
confidence: 99%